Association between controlling nutritional status (CONUT) score and amputation risk factors in T2DM patients with DFU - Xiang, Jie; Huang, Weijia; Gao, Wei; Tu, Yuanhui; Zhang, Yongsheng (Frontiers in Endocrinology, 2026)
BackgroundDiabetic foot ulcer (DFU) is one of the serious complications of type 2 diabetes (T2DM). Malnutrition is associated with amputation in DFU patients. We aimed to use the CONUT score to investigate the risk factors associated with DFU amputation.MethodsA retrospective analysis was conducted on 387 DFU patients admitted to the First Affiliated Hospital of Guangxi Medical University from January 2024 to June 2025. The patients were divided into non-amputation group (n=231) and amputation group (n=156). Additionally, patients were divided into three groups based on the CONUT score. Demographic characteristics, blood biochemical indicators, amputation rate were measured. Multiple linear regression analysis, multivariate binary logistic regression analysis, subgroup analysis and receiver operating characteristic (ROC) curve analysis were conducted.ResultsThe overall amputation rate of DFU patients was 40.3%. The amputation group had longer hospital stays, larger foot ulcer areas, higher incidence of osteomyelitis and peripheral arterial disease (PAD) than those without amputation. In addition, the amputees had lower levels of albumin, prealbumin, hemoglobin and prognostic nutritional index, but higher levels of WBC, ESR, and CONUT score. As the CONUT score increased, the amputation rate of patients also increased. Logistic regression found that CONUT score, osteomyelitis and PAD were independent risk factors of amputation in DFU patients. Subgroups analysis showed CONUT score remained significantly associated with DFU amputation in the subgroups except in patients with HbA1c < 7%. ROC analysis showed that the AUC was 0.705 (95% CI: 0.652–0.758, p<0.001), indicating that CONUT score had good predictive performance for DFU amputation.ConclusionCONUT score was associated with amputation in DFU patients. Early assessment of the patient’s nutritional status and improvement of malnutrition can reduce the risk of amputation.